(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Job satisfaction is one of the most important fruit for employee to work in a sustainable and effective manner. Today the highly competitive world putting pressure on employees to perform and the performance of the employee depend on many factors out of which job satisfaction is crucial one. Day to day functioning of the employee will be disturbed in long run if heshe not satisfy with their job. Job satisfaction provide motivation to employees to work and heart fullness. The level of motivation impact on employee performance and that impact organization performance. The Satisfaction of employees depends on various factors like salary, autonomy, parks, working environment etc and it is very important to pay attention towards the employees to make them satisfy. Satisfaction of employees is related with the performance of an individual, employee. The study was conducted to check the Satisfaction level of employees in organization whether these are curricular activities or non-curricular activities. The sample comprised of 60 employees of bank. Being a quantitative data, the scores were analyzed with the help of mean, ANOVA, Stander deviation and t-test developed by the researcher itself. The results unanimously identified that employee who are working in this organization are satisfy with their job are more happy during engagement and after engagement. The study also reveals that satisfaction level of employees’ directly related with financial compensation and monitory earning escalate the performance of employees and that escalate organization performance.